From Traditional Resource to Global Commodities:—A Comparison of Rhodiola Species Using NMR Spectroscopy—Metabolomics and HPTLC - Booker, Anthony; Zhai, Lixiang; Gkouva, Christina; Li, Shuyuan; Heinrich, Michael (Frontiers in Pharmacology, 2016)
The fast developing international trade of products based on traditional knowledge and their value chains has become an important aspect of the ethnopharmacological debate. The structure and diversity of value chains and their impact on the phytochemical composition of herbal medicinal products, as well as the underlying government policies and regulations, have been overlooked in the debate about quality problems in transnational trade. Rhodiola species, including Rhodiola rosea L. and Rhodiola crenulata (Hook. f. & Thomson) H. Ohba, are used as traditional herbal medicines. Faced with resource depletion and environment destruction, R. rosea and R. crenulata are becoming endangered, making them more economically valuable to collectors and middlemen, and also increasing the risk of adulteration and low quality. Rhodiola products have been subject to adulteration and we recently assessed 39 commercial products for their composition and quality. However, the range of Rhodiola species potentially implicated has not been assessed. Also, the ability of selected analytical techniques in differentiating these species is not known yet. Using a strategy previously developed by our group, we compare the phytochemical differences among Rhodiola raw materials available on the market to provide a practical method for the identification of different Rhodiola species from Europe and Asia and the detection of potential adulterants. Nuclear magnetic resonance spectroscopy coupled with multivariate analysis software and high performance thin layer chromatography techniques were used to analyse the samples. Rosavin and rosarin were mainly present in R. rosea but also in Rosea sachalinensis Borris. 30% of the Rhodiola samples purchased from the Chinese market were adulterated by other Rhodiola spp. The utilization of a combined platform based on 1H-NMR and HPTLC methods resulted in an integrated analysis of different Rhodiola species. We identified adulteration at the earliest stage of the value chains, i.e., during collection as a key problem involving several species. This project also highlights the need to further study the links between producers and consumers in national and trans-national trade.